NILAI KEARIFAN LOKAL BUDAYA KENDURI DI PULAU BENGKALIS DITINJAU DARI ASPEK AGAMIS DAN SOSIOLOGIS - Mursela, Mursela; Kamila, Yuyun; Nurjihad, Riko (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Local wisdom in the kenduri culture of Bengkalis Island is one of the rich and highly valuable cultural heritages. This research aims to identify the local wisdom values of the kenduri culture in Bengkalis Island from both religious and sociological aspects. This research uses a qualitative approach with observation, interview, and literature study methods. The results show that the kenduri culture in Bengkalis Island has high local wisdom values in the religious aspect through fulfilling the rules of religion in conducting traditional events. Meanwhile, in the sociological aspect, the kenduri culture in Bengkalis Island shows local wisdom in strengthening social relationships among community members, enhancing family and brotherhood bonds, and reinforcing social values such as mutual cooperation and togetherness in the community. However, the kenduri culture in Bengkalis Island also faces challenges in its development in modern times. To preserve and maintain the local wisdom values of the kenduri culture in Bengkalis Island, comprehensive preservation efforts involving all levels of society are necessary